Gender-Responsive Participatory Variety Selection in Kenya: Implications for Common Bean (Phaseolus vulgaris L.) Breeding in Kenya - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu (2024)
The data collection aimed to investigate gender-responsive participatory variety selection (PVS) for common bean breeding in Kenya. It was conducted across Embu and Nakuru Counties in 2019 to understand gender differences in varietal and trait preferences among farmers. The study focused on preferences for biofortified released and local bean varieties, covering major topics like yield, maturity, pest resistance, marketability, and cooking time. The Principal Investigators sought to identify gender-specific adoption barriers, potential trade-offs, and socio-economic influences on varietal preferences.